Changes in Resting-State Cerebral Activity in Women With Polycystic Ovary Syndrome: A Functional MR Imaging Study - Li, Guanghui; Hu, Junhao; Zhang, Si; Fan, Weijie; Wen, Li; Wang, Guangxian; Zhang, Dong (Frontiers in Endocrinology, 2020)
Background: Previous studies have found that women with polycystic ovary syndrome (PCOS) have some degree of brain function change as well as cognitive function and emotions, which might be associated with abnormal sex hormones and insulin resistance (IR). However, the underlying neurobiological mechanisms between these alterations and abnormal hormone levels have not yet been clarified. Method: Fasting serum hormone testing, neuropsychological testing and resting-state magnetic resonance imaging (rs-fMRI) were performed in 41 women with newly diagnosed PCOS and 41 healthy controls matched by age and education during their 2-5 day menstrual period. Analysis of the amplitude of low-frequency fluctuation (ALFF) was used to calculate the seed points. Then, functional connectivity (FC) between these abnormal seed points and other voxels in the whole brain was calculated. Finally, the correlations between clinical indexes, neuropsychological evaluation scores and neuroimaging data were analyzed. Results: Compared with the control group, the PCOS group showed higher testosterone (T), luteinizing hormone (LH) and fasting insulin (FINS) levels; worse sleep quality; increased depressive and anxiety state scores; and memory and executive function impairments. Simultaneously, neuroimaging results showed abnormal ALFF value and FC in some certain brain regions. By analyzing the correlations between ALFF values and FC in these brain regions as well as evaluating hormone levels and behavioral results, we observed that the ALFF value in the MFG.L was negatively correlated with the plasma FINS level in subjects with IR and that the increased FC strength between the MFG.L and IFG.L was positively correlated with the serum T level. Also, the FC strength between the PCG.L and IFGtriang.L was negatively correlated with the plasma LH level; moreover, the decreased FC strength between the MOG.R and IOG.R was associated with two-back task accuracy. Conclusion: Aberrant cerebral activity at the regional and network levels in women with PCOS was associated with high circulating levels of T, LH and FINS, which may provide useful information regarding the potential mechanisms of cognitive impairment and emotional changes in this population.